Exploring Teachers’ Support for the Academic Recovery and Accessible Learning (ARAL-Reading) Program: A Qualitative Study of School-Based Reading Intervention - PELAGIO, DANEVA MAE; PASCUAL, REY (Studies in Technology and Education, 2026)
This qualitative study explored teachers’ support for the Academic Recovery and Accessible Learning (ARAL-Reading) Program at Maddela South Central School. The study aimed to examine teachers’ experiences, instructional practices, and support mechanisms in implementing school-based reading interventions for struggling readers within the context of the ARAL-Reading Program. Using a descriptive qualitative research design, data were gathered through semi-structured interviews, classroom observations, and document analysis involving teachers and selected learners participating in the reading intervention program. Thematic analysis revealed four major themes: (1) learner-centered and remedial reading instructional practices, (2) collaborative teacher support and learner motivation, (3) contextualized and adaptive literacy intervention strategies, and (4) challenges in implementing school-based reading recovery programs. Findings showed that teachers demonstrated strong commitment and instructional adaptability in supporting struggling readers through differentiated reading activities, individualized guidance, peer-assisted learning, and contextualized literacy materials. Learners became more engaged and confident when reading instruction was interactive, supportive, and aligned with their reading levels and learning needs. However, limited instructional resources, time constraints, learner diversity, and insufficient parental support affected the implementation of the ARAL-Reading Program. The study concludes that teacher support and learner-centered intervention practices significantly contribute to learners’ reading engagement, confidence, and literacy improvement. Strengthening literacy resources, institutional support, and teacher professional development is recommended to improve school-based reading intervention programs in public elementary schools.